Factors Affecting the Patients' Quality of Life after Coronary Artery Bypass Graft - Sedigheh Behrouzifar; Shayesteh Zenouzi; Mohammadhassan Nezafati; Habiballah Esmaili (Iran University of Medical Sciences, 2009)
Background & Aim: Because of increasing growth of treatment in coronary artery disease patients by revascularization techniques, and the importance of recovery and promotion of quality of life, information about the factors affecting quality of life after coronary artery bypass graft can be useful to determine prognosis and to eliminate or minimize modifiable factors. So, the aim of the present study was to determine the factors affecting patients' quality of life 10 weeks after surgery.   Material & Method: This research was a descriptive-analytical and longitudinal study. Ninety one patients referring to the department of open heart surgery of Imam Reza Hospital in Mashad City during 2005-2006 were selected according to inclusion and exclusion criteria. Data were collected by interview in 3 stages, 24 hours before surgery, 6 weeks and 10 weeks after surgery. Quality of life was measured by SF 36 short form. Data were analyzed by SPSS.   Results: According to the findings, Variables as age (P=0.04), gender (P=0.004), marital status (P=0.02), literacy level (P=0.04), number of cigarettes smoked daily (P=0.002), using beta-blockers before surgery (P=0.04), hemoglobin on admission (P=0.002), duration of mechanical ventilation (P=0.003), participating in physical exercises after surgery (P=0.01) and sleep quality 6 weeks after surgery (P=0.006) had an effect on quality of life 10 weeks after surgery.   Conclusion: The results demonstrated that implementing supportive actions in women and elders to progress process of recovery, providing interpersonal supports in patients with late spouse, increasing information about the disease in illiterate and little literate clients, treating anemia, ceasing smoking and participating at physical exercises after surgery may be effective to improve quality of life after surgery.